ATF-1CREB heterodimer is involved in constitutive expression of the housekeeping Na,K-ATPase alpha 1 subunit gene. - Kobayashi, M (1995)
Na,K-ATPase alpha 1 subunit is an essential protein for cell growth and homeostasis. The gene coding for the protein is expressed in various types of tissues. We previously demonstrated that the transcription regulatory element of the gene (ARE) is located in the position -102 to -61 from the transcription initiation site. To identify the minimal regions that are essential for the constitutive expression, the sequences of the ARE were analyzed in detail by in vitro transcription assays using nuclear extracts from rat kidney, brain and liver. The analyses of various mutations in the promoter demonstrated that the proximal region of the ARE is required for the efficient transcription in every nuclear extract. The factors binding to this region in these nuclear extracts exhibited identical mobility in gel retardation assays. The ATF/CRE core motif is indicated to be important for the factor binding and for the promoter function in all nuclear extracts. The common binding factor in the nuclear extracts was revealed to be an ATF-1/CREB heterodimer by gel retardation assays using specific antibodies. We conclude that the ATF-1/CREB heterodimer is involved in the constitutive expression of the Na,K-ATPase alpha 1 subunit gene.